1-(2,4-Difluorophenyl)thiourea - Fun, Hoong-Kun (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, C(7)H(6)F(2)N(2)S, consists of two independent molecules, with comparable geometries. In one molecule, the thiourea moiety is essentially planar (r.m.s. deviation = 0.014 Å) and it forms a dihedral angle of 78.67 (9)° with the benzene ring. The corresponding r.m.s. deviation and dihedral angle for the other molecule are 0.011 Å and 81.71 (8)°, respectively. In both molecules, one of the F atoms is disordered over two positions with refined site occupancies of 0.572 (3):0.428 (3) and 0.909 (2):0.091 (2), respectively. In the crystal, molecules are linked via N—H⋯S and C—H⋯F hydrogen bonds into two-dimensional networks parallel to (010).